Alkaline Phosphatase as Marker of Hepatocellular Carcinoma: Alkaline Phosphatase as Marker of Hepatocellular Carcinoma - Hussain, Atif; Khan, Bahawal; Ziauddin, .; Asmatullah, .; Anwar, Muhammad; Haq, Noman ul (Pakistan Journal of Health Sciences, 2024)
Hepatocellular carcinoma (HCC), the fifth most common cancer worldwide, is often detected at a late stage and is frequently fatal.. Liver resection is the main treatment for cases originating from normal liver tissue, but most cases arise from diseased liver parenchyma, such as HBV-related cirrhosis. While many studies link alkaline phosphatase (ALP) to HCC, its diagnostic accuracy in distinguishing HCC from other liver disorders remains limited.. Objective: To assess the diagnostic accuracy of rising ALP levels as an indicator for hepatocellular carcinoma. Methods: The cross-sectional study at Sheikh Zayed Hospital, Lahore, included 130 non-probability sampled patients. Individuals aged 18–65 suspected of first-time hepatocellular carcinoma (HCC) were included, excluding those with prior HCC diagnosis or biliary obstructions. Triphasic CT scans confirmed HCC and assessed ALP/AFP. Data were analyzed using SPSS version 23.0, showing numerical variables as mean ± SD and categorical variables as frequency/percentage. Results: In 130 patients, ALP-based detection outperformed CT scans (81.40%, 9.20%) in sensitivity (93.00%) and positive predictive value (95.00%). HCC detection and performance vary greatly by age and gender. ALP is sensitive across age (95.00%) and gender (98.00% male, 86.00% female). In 108 positive (83.08%) and 22 negative (16.92%) HCC detections on ALP, demographics affect specificity, supporting nuanced ALP interpretation for accurate HCC diagnosis. Conclusions: Elevated ALP levels serve as risk predictors in HCC patients. The prognostic model proposed in this study has the potential to influence outcomes for patients across different risk groups.